Oar blade force coefficients and a mathematical model of rowing - Coppel, A.; Gardner, T.; Caplan, N.; Hargreaves, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The aim of this study was to validate the use of computational fluid dynamics (CFD) to determine oar blade force coefficients for use in a mathematical model of rowing mechanics to predict the performance of a boat. Experimental and CFD derived lift and drag force coefficients for a Macon oar blade were taken from previously published research. Each set of coefficients was used to drive a mathematical model of rowing, and predicted instantaneous and mean steady state boat velocity compared. Instantaneous boat velocity was similar throughout the stroke and mean boat velocity varied by only 1.33%. In conclusion, this investigation has demonstrated that lift and drag coefficients obtained by computational methods may be used successfully to predict boat behaviour in a mathematical model of rowing. The use of computational data closely matches model outputs derived from experimental data.